The art and science of recruitment to a cancer rapid autopsy programme: A qualitative study exploring patient and clinician experiences. (February 2021) - Tutty, Erin; Horsley, Philomena; Forbes Shepherd, Rowan; Forrest, Laura E.
Background: CASCADE is a successful, Australia-first cancer rapid autopsy programme. Patients are recruited to the programme by their clinician once they understand that further treatment has only palliative intent. Despite its value, rapid autopsy is a rare research method owing partly to recruitment challenges. Aim: This research aimed to explore (1) how, in practice, clinicians select and recruit patients to the programme and (2) patient experiences of this process. Design: This was a qualitative study grounded in phenomenology. CASCADE team members (clinicians and researchers) and patients participated in semi-structured interviews. Data were analysed using an inductive, team-based approach to thematic analysis. Participants: Interviews were conducted with 31 participants (11 patients and 20 CASCADE team members). Results: Patient selection and recruitment to a rapid autopsy programme is both an art and science. In practice, patient selection is a subjective process that involves assessing a patient's psychosocial suitability for the programme. Trust and rapport are necessary for informing this assessment and to create an environment conducive to discussing rapid autopsy. Clinicians have also crafted their own ways of delivering information about CASCADE, with both clinicians and patients acknowledging that, if not handled sensitively, recruitment could cause distress. Overall, patients were satisfied with the way in which they were recruited. Conclusion: Findings provide insight into how clinicians successfully select and recruit patients to a rapid autopsy programme and suggests that discussing such topics are acceptable to end-of-life patients. This research also raises thought-provoking questions about the 'gatekeeping' role of clinicians in recruitment.